Pentingnya Pendidikan Kristen dalam Membangun Kerohanian Keluarga di Masa Pandemi Covid-19 - Arifianto, Yonatan Alex (Regula Fidei : Jurnal Pendidikan Agama Kristen, 2020)
The covid-19 pandemic brought disaster in all aspects of the world including formal and Christian education carried out by the church. So that the church and all believers must obey government regulations. The corona virus epidemic also affects the psychology and spirituality of believers. Therefore, families based on the importance of PAK in building family spirituality during the Covid-19 pandemic can be understood and carried out to build trust and knowledge of God and can be an answer for those who are discouraged in the midst of the Covid-19 pandemic. The author conducted a study using the literature method with a qualitative descriptive approach in order to be able to find benefits for Christian families, at this time in the 19th and post-epidemics. The importance of building spirituality in the family can be done first, understanding the basis and purpose of Christian religious education and family in building spirituality. Then it is grounded that the Bible as a spiritual foundation in the family and family must work together to become servants who equip family life in spirituality that is increasingly pleasing before God and a blessing to others because there is value and fruit that is produced through the important role of PAK in building family spirituality in the future. the Covid-19 pandemic. Abstrak Pandemi Covid-19 membawa bencana dalam segala aspek di dunia termasuk bagi pendidikan formal maupun pendidikan Kristen yang dilakukan oleh gereja. Sehingga gereja dan seluruh orang percaya wajib mentaati peraturan pemerintah. Wabah penyakit virus corona juga mempengaruhi psikologi dan kerohanian orang percaya. Maka itu keluarga berdasarkan Pentingnya PAK dalam membangun kerohanian keluarga di masa pandemi Covid-19 dapat dipahami dan dilakukan untuk membangun iman percaya dan pengenalan akan Tuhan serta dapat menjadi jawaban bagi mereka yang putus asa ditengah pandemic Covid-19. Penulis melakukan kajian menggunakan metode pustaka dengan pendekatan kualitatif deskriptif supaya dapat menemukan manfaat bagi keluarga Kristen, saat ini dimasa Covid-19 maupun pasca wabah ini. Pentingnya membangun kerohanian dalam keluarga dapat dilakukan dengan pertama, memahami landasan dan tujuan pendidikan agama Kristen dan keluarga dalam membangun kerohanian. Lalu mendasari bahwa Alkitab sebagai Dasar fondasi kerohanian dalam Keluarga dan keluarga harus bekerja sama menjadi pelayan yang memperlengkapi kehidupan keluarga dalam kerohanian yang semakin berkenan dihadapan Tuhan dan menjadi berkat bagi sesama karena ada nilai dan buah yang dihasilkan lewat peran pentingnya PAK dalam membangun kerohanian keluarga di masa pandemi Covid-19.